(3eTGQb GdCfhGQ GdfHhjI ef UMGM GdCNHGQ GdeUWahjIs - (3QVj GdOjf CHj GdaVGFd GdMSf Hf eMeO CHh GdMSf, MjOQ GdUGZGfj, J (B650 (3g` s ((3eMeO Hf Ydi YQH Hf MSf GdedWi s)
(3ChdgG (B:s
(3jHOC GdehLhO efg Hbhdg (B: (3MOKfG CHh gQjQI QVi Gddg Yfg (B: (3ef NQL ef GdWGYI haGQb GdLeGYI aeGJ eGJ eJjI LGgdjI s
(3BNQgG (B:s
(3CfS QVi Gddg Yfg (B: (3dHjc YeQh hMLG JeJ HYhf Gddg hMSf Jhajbg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B214s
Keywords: (3GdMOjK h GdeUWdMs